Hello my friend,,, While i'm studying the DSP course , I faced this problem as attached photo please help me about this theorem states Ʃ1 = N+1.. thanks in advance..
You are reading the theorem wrong. You have a sum of terms, the number of terms is from n=0 to N. Let say you have one term, the first term is n=0, since you only have one term then N=0 too. So the sum of terms is u^2(0)=1^2=1. Since N=0, then N+1=0+1=1. So. u^2(0)=N+1 Now lets do two terms. First term is n=0. Second term is n=1. N=1 because we are doing two terms where first term is n=0, second term is n=1. u^2(0)+u^2(1)=1^2+1^2=1+1=2 N+1=1+1=2 So. u^2(0)+u^2(1)=N+1 And so on.